2013
DOI: 10.1186/1754-6834-6-14
|View full text |Cite
|
Sign up to set email alerts
|

Survey of renewable chemicals produced from lignocellulosic biomass during ionic liquid pretreatment

Abstract: BackgroundLignin is often overlooked in the valorization of lignocellulosic biomass, but lignin-based materials and chemicals represent potential value-added products for biorefineries that could significantly improve the economics of a biorefinery. Fluctuating crude oil prices and changing fuel specifications are some of the driving factors to develop new technologies that could be used to convert polymeric lignin into low molecular weight lignin and or monomeric aromatic feedstocks to assist in the displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 27 publications
2
97
1
3
Order By: Relevance
“…The fact that products obtained from oxidation reactions were mainly G-lignin derived compounds corroborates the G-lignin rich source. Similar profile of compounds were reported in a previous study using [C2C1Im][OAc] IL for the pretreatment of switchgrass, eucalyptus, and Kraft lignin (Varanasi et al, 2013). In another study, Stärk et al (2010) reported similar product profiles from the catalytic oxidation of organosolv beech wood lignin with guaiacol as the main product probably due to the cleavage of β-aryl ether bond.…”
Section: Lignin Breakdown Product Identificationsupporting
confidence: 66%
“…The fact that products obtained from oxidation reactions were mainly G-lignin derived compounds corroborates the G-lignin rich source. Similar profile of compounds were reported in a previous study using [C2C1Im][OAc] IL for the pretreatment of switchgrass, eucalyptus, and Kraft lignin (Varanasi et al, 2013). In another study, Stärk et al (2010) reported similar product profiles from the catalytic oxidation of organosolv beech wood lignin with guaiacol as the main product probably due to the cleavage of β-aryl ether bond.…”
Section: Lignin Breakdown Product Identificationsupporting
confidence: 66%
“…Due to the highly aromatic structure of lignin, different processes have been developed that break down lignin molecules to produce other valuable aromatic chemicals, such as benzene, toluene, xylene, styrene, phenols, cyclohexane, aromatic aldehydes, vanillin, and vanillic acid (da Silva et al, 2009;Varanasi et al, 2013;Yamaguchi et al, 2017). Since lignin is a polyol, different synthesis techniques have also been used to study the effect of lignin incorporation on the properties of biodegradable polymer materials.…”
Section: Ligninmentioning
confidence: 99%
“…Lignin is also the largest renewable source of biopolymers [9]. However, unlike cellulose and hemicellulose, lignin has received limited attention and its potential has been underutilized with regard to valorization [6,10]. The main reason for the limited interest is that, unlike cellulose and hemicellulose which are easily convertible fractions of wood, the heterogeneous and cross-linked structure of the lignin molecule complicates its controlled depolymerization into single chemicals [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for the limited interest is that, unlike cellulose and hemicellulose which are easily convertible fractions of wood, the heterogeneous and cross-linked structure of the lignin molecule complicates its controlled depolymerization into single chemicals [3,9]. Nevertheless, it is clear that lignin holds promise as a significant resource for the production of a wide range of renewable chemicals, due to its high energy content, its aromatic structure, the presence of highly reactive groups, and the fact that it will be generated in large quantities as second-generation biorefineries are deployed [10].…”
Section: Introductionmentioning
confidence: 99%